OPEN GOVERNMENT AT GRASSROOTS LEVEL GOVERNMENT: E-GOVERNMENT SUCCESS FACTORS IN THE VILLAGE OF PEJAMBON, BOJONEGORO - Mr. Kusnan (DIA: Jurnal Administrasi Publik, 2020)
The Government of Bojonegoro Regency was an Indonesia representative in Open Government Partnership (OGP) of Subnational Government Pilot Program. This achievement raised new energy to implement openness in rural government. This policy was also in line with Rural Law. Mean while, to implement government openness, the use of e-Government was highly prioritized. By e-Government, the governance would be effective and efficient. However, only one of 419 villages in Bojonegoro succesded in implementing government openness, that was Pejambon Village. This village won the best website in East Java in 2016 and 2017. There after, it took the first place as the most informative and transparant village in national level in 2018. This research uses qualitative descriptive research methods. The results show that in general the success of E-Government implementation in the open government in Pejambon village is influenced by three main factors. First governing factors that include vision, leadership, and funding. Second, organizational factors that include policy, human resources, and collaboration. Third, technical factors that include IT infrastructure and IT standars. However, there are some indicators that need to get attention and improved by the village government of Pejambon, namely Funding, human resources, and IT infrastructure. If not immediately handled seriously, the future will impede the implementation of open government in Pejambon village.Keywords: Open Government, Succes Factors, e-Government, Grassroots, Village